# Solve for t 9tsp=tbsp 9tsp=tbsp
Subtract tbsp from both sides of the equation.
9tsp-tbsp=0
Factor tsp out of 9tsp-tbsp.
Factor tsp out of 9tsp.
tsp(9)-tbsp=0
Factor tsp out of -tbsp.
tsp(9)+tsp(-1b)=0
Factor tsp out of tsp(9)+tsp(-1b).
tsp(9-1b)=0
tsp(9-1b)=0
Rewrite -1b as -b.
tsp(9-b)=0
Divide each term by sp(9-b) and simplify.
Divide each term in tsp(9-b)=0 by sp(9-b).
tsp(9-b)sp(9-b)=0sp(9-b)
Simplify tsp(9-b)sp(9-b).
Cancel the common factor of s.
Cancel the common factor.
tsp(9-b)sp(9-b)=0sp(9-b)
Rewrite the expression.
tp(9-b)p(9-b)=0sp(9-b)
tp(9-b)p(9-b)=0sp(9-b)
Cancel the common factor of p.
Cancel the common factor.
tp(9-b)p(9-b)=0sp(9-b)
Rewrite the expression.
t(9-b)9-b=0sp(9-b)
t(9-b)9-b=0sp(9-b)
Cancel the common factor of 9-b.
Cancel the common factor.
t(9-b)9-b=0sp(9-b)
Divide t by 1.
t=0sp(9-b)
t=0sp(9-b)
t=0sp(9-b)
Divide 0 by sp(9-b).
t=0
t=0
Solve for t 9tsp=tbsp

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top